2003
DOI: 10.1021/ol034555l
|View full text |Cite
|
Sign up to set email alerts
|

Relative Rates of Michael Reactions of 2‘-(Phenethyl)thiol with Vinyl Sulfones, Vinyl Sulfonate Esters, and Vinyl Sulfonamides Relevant to Vinyl Sulfonyl Cysteine Protease Inhibitors

Abstract: [reaction: see text] The relative rates of Michael additions of 2'-(phenethyl)thiol to representative vinyl sulfonyl Michael acceptors were measured. The dependence of the reactivity of the Michael acceptor on the nature of the sulfonyl R substituent was determined in order to evaluate the effect of these substituents on the inactivation kinetics of comparably substituted vinyl sulfonyl cysteine protease inhibitors. The rates of these Michael additions vary over 3 orders of magnitude, with phenyl vinyl sulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 24 publications
5
65
0
2
Order By: Relevance
“…It is interesting to note that other benzyl-substituted pyrazolopyrimidines bearing similar electrophiles such as an acrylamide (7) and an α-chloroacetamide (12) were poor inhibitors. In the former case, this fact may be because the double bond of the vinylsulfonamide (9) is expected to have greater rotational freedom than the planar acrylamide (7) as a result of the poor overlap between the sp 3 ∕d orbitals of nitrogen and sulfur, respectively (37). In the instance of the α-chloroacetamide, it is possible that the electrophile/nucleophile pair is unable to assume an orientation compatible with S N 2 attack.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that other benzyl-substituted pyrazolopyrimidines bearing similar electrophiles such as an acrylamide (7) and an α-chloroacetamide (12) were poor inhibitors. In the former case, this fact may be because the double bond of the vinylsulfonamide (9) is expected to have greater rotational freedom than the planar acrylamide (7) as a result of the poor overlap between the sp 3 ∕d orbitals of nitrogen and sulfur, respectively (37). In the instance of the α-chloroacetamide, it is possible that the electrophile/nucleophile pair is unable to assume an orientation compatible with S N 2 attack.…”
Section: Discussionmentioning
confidence: 99%
“…Roush and co-workers recently ranked the relative activities of Michael acceptors: enone > vinylsulfone > vinylsulfonate > enoate > vinylsulfonamide. 5 The vinylsulfonamide was chosen initially since this is the least reactive member in the series to minimize nonspecific thiol addition. Additionally, molecular modeling showed that the vinylsulfonamide adopted the required folded conformation of the bound acyladenylate ( Figure S11, Supporting Information).…”
mentioning
confidence: 99%
“…[118] The vinyl sulfonamide was found to be the least reactive, with the rate of thiol addition to phenyl vinyl sulfonate esters proceeding approximately 3000 times faster. This suggested the vinyl sulfonamide as a potential group for use in KTGT, as it is less likely to react non-selectively than other Michael acceptors.…”
Section: Vinyl Sulfonamidementioning
confidence: 98%